2013
DOI: 10.5812/atr..12501
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Ischemia and Reperfusion Injury and Trauma: Current Concepts

Abstract: Context: Ischemia-reperfusion injury is a fascinating topic which has drawn a lot of interest in the last several years. Hepatic ischemia reperfusion injury may occur in a variety of clinical situations. These include transplantation, liver resection, trauma, and vascular surgery. Evidence Acquisition: The purpose of this review was to outline the molecular mechanisms underlying hepatic I/R injury and present the latest approaches, both surgical and pharmacological, regarding the prevention of it. A comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 75 publications
1
24
0
Order By: Relevance
“…Many experimental and clinical studies have shown that IPostC is a simple and safe approach to increase protection against damages caused by IR insults to various organs such as the heart, brain, kidney, liver, intestine, lung, skeletal muscle and spinal cord . Despite the effectiveness of this method in various organs of humans and experimental models, many fundamental questions linked to the protective effects of IPostC are still unanswered.…”
Section: Ipostc Protocols In Various Tissues and Its Algorithmsmentioning
confidence: 99%
“…Many experimental and clinical studies have shown that IPostC is a simple and safe approach to increase protection against damages caused by IR insults to various organs such as the heart, brain, kidney, liver, intestine, lung, skeletal muscle and spinal cord . Despite the effectiveness of this method in various organs of humans and experimental models, many fundamental questions linked to the protective effects of IPostC are still unanswered.…”
Section: Ipostc Protocols In Various Tissues and Its Algorithmsmentioning
confidence: 99%
“…Th erefore, many studies have focused on minimizing the adverse eff ects of I/R injury. Surgery, pharmacologic strategies, and gene therapy are the major methods currently used to alleviate I/R injury (Papadopoulos et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The intermittent Pringle maneuver, a temporary clamping of the hepatoduodenal ligament, is a safe and useful procedure to reduce blood loss during liver resection. However, the intermittent Pringle maneuver does carry a risk of ischemia‐reperfusion injury to the liver, which is defined as an inflammatory response and organ damage, triggered by ischemia inducing hypoxic stress and reperfusion inducing oxidative stress . Numerous factors contribute to hepatic ischemia‐reperfusion injury, with activation of Kupffer cells, induction of oxidative stress, and upregulation of proinflammatory cytokine signaling .…”
Section: Discussionmentioning
confidence: 99%